(untitled) (Journal of Environmental Bioremediation and Toxicology, 2014)
Diesel is a toxic xenobiotic. However, some bacteria are capable of using diesel as a carbon source for energy and growth. At high diesel concentration, an inhibition to the growth curves is seen. The study of the growth inhibitory properties of diesel on bacterium has often been carried out through the modelling of the specific growth rates obtained from the linearization of the growth curves of bacterium. Since there exists a variety of models for obtaining a more accurate specific growth rates from bacterial growth curves such as logistic, Gompertz, Richards, Schnute, Baranyi-Roberts, Von Bertalanffy, Buchanan three-phase and more recently Huang models, the use of these models over the simplification through linearization is needed. The modified Gompertz model gave the best fitting based on statistical test with the lowest values for RMSE and corrected Akaike Information Criteria, the highest value for adjusted R2 and the closest values to unity for both Accuracy and Bias factors. The modified Gompertz model is thus the best model to obtain specific growth rates from the growth curves of Acinetobacter sp. strain DRY12 grown on diesel.